PENERAPAN SANKSI BAGI WAJIB PAJAK RESTORAN DI KOTA PEKANBARU - David Halomoan Rumapea; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Aplication Of Sanctions For Tax Payers Restaurant for current needs goverment attention where not maximal Income Office Region of Pekanbaru Area, among them: increasing the number of restaurant that are not followed by an increase in the restaurant tax, many restaurants that do not pay taxes, not the realization tax target restaurants. Formulation of the problem in research is hoh to aplication of sanctions for taxpayers restaurants in the city of pekanbaru and what factors influence factors that affect The Aplication Of Sanctions For Tax Payers Restauran.The purpose of this research is to know and analysis The Aplication Of Sanctions For Tax Payers Restauran and to know and analysis factors influence factors that affect Aplication Of Sanctions For Tax Payers Restauran . This research use Van Meter Van Horn Teory with indicator: standard and target, resource, communication between organizations , executor characteristic, implementor disposition, social condition environment, economy and political..This research methods is using exploratory qualitative approach. Informants in this research are member income office region of Pekanbaru, civil service policy unit agency of Pekanbaru, restaurateur. Data collection techniques in this research are interviews, observation and documentation.The results of this research is the The Aplication Of Sanctions For Tax Payers Restauran not less maximal. Still many restorant that do not pay taxes, number of restaurant tax is not in creasing sanctions aplied not according to the rules. Influence factors that affect Aplication Of Sanctions For Tax Payers Restauran in Pekanbaru City are resource, and coordination.Keywords: Aplication Of Sanctions and Restaurant Tax